KAJIAN STUDI KRITIS IMPLIKASI SLOGAN PAJAK “BANGGA BAYAR PAJAK” - Haryadi, Bambang; Zahra, Lailatuz (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2022)
The purpose of this study was to test the level of knowledge and understanding of taxpayers about tax slogans "proud to pay taxes." The type of research is a descriptive qualitative method using a critical approach. The place chosen in this study was KPP Pratama Pamekasan. The results showed that (1) socialization by KPP Pratama Pamekasan was still lacking, so the community did not know and understand what he wanted in the slogan. (2) The slogan is still interpreted and is inappropriate. The taxpayer still considers the slogan to remind the awareness to pay taxes. Not yet at the stage of pride for taxpayers after paying taxes; (3) Great hope of the slogan that the community is more proud of the government can manage professionally and accountable tax revenues.